Effectiveness of nursing educational interventions in managing post-surgical pain. Systematic review - Antonio Reaza-Alarcón; Beatriz Rodríguez Martín (Universidad de Antioquia, 2019)
Objective. Analyze and integrate studies that inquire on the benefits of nursing educational interventions to manage post-surgical pain. Methods. A systematic search was conducted in the databases of Scopus, Medline (Pubmed), Web of Science, The Cochrane Library, and CINAHL of systematic reviews, randomized clinical trials, and quasiexperimental studies published in English and Spanish until 2018 that analyzed the effectiveness of educational interventions in managing post-surgical pain in adult patients. Results. Twelve studies complied inclusion criteria, of which nine reported less pain in the group receiving the educational intervention. These interventions also helped to diminish the level of anxiety and improved functionality to perform activities of daily life. The level of quality of the studies was medium. Conclusion. Although the review showed that nursing educational interventions could influence on the relief of post-surgical pain, more rigorous studies are necessary, with bigger sample sizes and higher methodological quality, which help to establish the real effectiveness in managing post-surgical patients with pain.   How to cite this article: Reaza-Alarcón A, RodríguezMartín B. Effectiveness of nursing educational interventions in managing post-surgical pain. Systematic review. Invest. Educ. Enferm. 2019; 37(2):e10.